Pengaruh Demografi, Transportasi dan Sosial Ekonomi terhadap Kepatuhan ANC (Antenatal Care) di Puskesmas Lawonda Kabupaten Sumba Tengah - Likka, Elisantri Rambu Saja Enga; Umiastuti, Pirlina; Prasetyo, Budi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to analyze the influence of demographics, transportation and socio-economics on ANC compliance. This research method is observational with a cross sectional research design. The total sample was 65 pregnant women with a sampling technique, namely purposive sampling of 28 pregnant women who came to the community health center and accidental sampling of 37 pregnant women who came to the class for pregnant women and posyandu for toddlers. The instrument used was a questionnaire, data analysis used the chi square test and Fisher's Exact. The research results showed that pregnancy distance, distance from home, travel time, maternal education, maternal knowledge, husband's occupation, husband's income, marital status and husband/family support had an influence on ANC compliance. The factors that have the greatest influence are husband/family support and mother's knowledge.